Evaluation of Grain Yield of Heat Stress Resilient Maize Hybrids in Nepal - Koirala, Keshab Babu; Giri, Yagya Prasad; Rijal, Tirtha Raj; Zaidi, Pervez Haider; Sadananda, Ajanahalli Ramaiaha; Shrestha, Jiban (International Journal of Applied Sciences and Biotechnology, 2017)
Midhills, foot hills and river basin areas of are generally under spring maize cultivation. These areas along with the areas from Terai and Inner Terai where spring and early summer maize are grown are the most affected from heat stress. Identification and selection of suitable varieties and traits for high temperature tolerance is vital to produce heat resilient genotypes.With a view to identify high yielding heat stress resilient maize hybrids, genotypes received from International Maize and Wheat Improvement Centre (CIMMYT) were evaluated in alpha lattice design with two to three replications at Rampur, Nepalgunj and Surkhet in 2013/014, 2014/015 and 2015/016. Total 57 trials consisting of 7764 maize hyrbids were evaluated under heat stress conditions. At Nepalgunj and Surkhet, trials were planted in March/April. Out of the tested genotypes, 24 hybrids were found promising based on grain yield, plant and ear height. These 24 hybrids along with four National Maize Research Program (NMRP) developed and two multi-national companies’ hybrids as checks were tested in multilocation trials at Dumarwana, Nijgadh, Nawalparasi and Rampur in 2014/015. Out of these 24 hybrids, eight were selected and tested during 2015/016 in Dumarwana, Nijgadh, Nawalparasi, Anandapur and Rampur. Based on results combined over years and locations CAH-151 (8629 kg ha-1) and CAH-153 (8955 kg ha-1) were registered for general cultivation as Rampur Hybrid-8 and Rampur Hybrid-10, respectively. Other promising hybrids were CAH-1511 (8800 kg ha-1) followed by CAH-1515 (8678 kg ha-1), RML-95/RML-96 (8486 kg ha-1), CAH-1513 (8258 kg ha-1) and RML-86/RML-96 (7544 kg ha-1), respectively. Stability analysis revealed that CAH-151, CAH-153, CAH-1515, CAH-1511 and RML-95/RML-96 are stable hybrids having good performance.